2016
DOI: 10.12681/healthresj.19860
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarkıng ındıcators nursing workload ın Intensıve Care Unıts

Abstract: Introduction: The high and continues increasing nursing workload in the Intensive Care Unit (ICU) is a remarkable increase in mortality factor of heavy ill patients.Aim: The aim of this study was a comparison evaluation between the score of Nursing Workload (NW), Nursing Activity Score (NAS) and Comprehensive Nursing Intervention Score (CNIS) in nurses who treat critically ill patients in Intensive Care Unit (ICU).Material and Methods: The studied population was 100 patients who were hospitalized in Intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Mortality was 28.7%, much higher than in other studies, where mortality ranged from 13.5% to 13.64%. Conversely, in Dede et al [ 4 ] and Michali et al [ 3 ], a higher mortality was observed (46.7% and 41%, respectively), and even higher in Kollia et al [ 6 ], at the level of 71% [ 3 , 4 , 6 , 11 , 29 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mortality was 28.7%, much higher than in other studies, where mortality ranged from 13.5% to 13.64%. Conversely, in Dede et al [ 4 ] and Michali et al [ 3 ], a higher mortality was observed (46.7% and 41%, respectively), and even higher in Kollia et al [ 6 ], at the level of 71% [ 3 , 4 , 6 , 11 , 29 ].…”
Section: Discussionmentioning
confidence: 98%
“…Studies show that low nursing staffing rates are associated with a negative effect on patients’ health [ 3 , 4 ]. The development of NW monitoring and measurement systems is necessary to document the quality of health services provided, increase the professional satisfaction of nurses, and reduce the stress and burnout that are experienced frequently [ 5 , 6 ]. Nursing interventions in patients admitted in intensive care units (ICUs), if recorded on a daily basis, can be a predicting factor for patients’ outcomes and a tool for managing human and material resources effectively [ 7 ].…”
Section: Introductionmentioning
confidence: 99%